2003
DOI: 10.1002/ana.10746
|View full text |Cite
|
Sign up to set email alerts
|

Dually infected (HSV‐1/VZV) single neurons in human trigeminal ganglia

Abstract: Human trigeminal ganglia were tested by double fluorescence in situ hybridization for the presence and distribution of herpes simplex virus type 1 (HSV-1) and varicella-zoster virus (VZV) latency. Latency transcripts of both viruses were detected in common areas within the ganglia. Also, a few single neurons were shown to harbor HSV-1 and VZV together.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 19 publications
2
30
0
Order By: Relevance
“…Although VZV DNA can be detected in many different cell types during active infection, latency seems largely to be established in neural tissues, particularly in non-neuronal cells of sensory ganglia. [9][10][11]13,14 In the present study, VZV was detected in three of eight cases within only four sites: dorsal root ganglion, spinal cord, adrenal gland, and small intestine. VZV may maintain latency within the ganglion cells of the adrenal medulla and the parasympathetic ganglia of the small intestine.…”
Section: Discussionsupporting
confidence: 38%
See 3 more Smart Citations
“…Although VZV DNA can be detected in many different cell types during active infection, latency seems largely to be established in neural tissues, particularly in non-neuronal cells of sensory ganglia. [9][10][11]13,14 In the present study, VZV was detected in three of eight cases within only four sites: dorsal root ganglion, spinal cord, adrenal gland, and small intestine. VZV may maintain latency within the ganglion cells of the adrenal medulla and the parasympathetic ganglia of the small intestine.…”
Section: Discussionsupporting
confidence: 38%
“…Virus then spreads along the sensory nerves to sensory root ganglia where latency is established in ganglionic neurons. [9][10][11]13 HSV-1 was detected in four of eight cases. In two cases, HSV-1 was detected only in neural tissues (dorsal root ganglion, spinal cord, sympathetic ganglion, and peripheral nerve), whereas in two other cases, HSV-1 was detected in multiple tissues.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…As HSV and VZV both establish latency in sensory nerve ganglia, autopsy studies have predictably demonstrated the presence of both viruses in the same ganglia, even within the same neurons [6]. But despite their potential co-localization within the ganglion, the two viruses rarely cause simultaneous disease.…”
Section: Introductionmentioning
confidence: 99%